True uterus didelphys in she-camel: a case report and review of literature - Mahdy, Mohamed A. A.; Nasr Eldeen, Mohammed S. (Frontiers in Veterinary Science, 2024)
Background Uterus didelphys is a rare congenital anomaly of the female reproductive tract characterized by a divided uterine cervix and body. It occurs due to abnormal development of the paramesonephric (Müllerian) duct. Different forms of uterus didelphys have been reported in several animal species, including bovine, equine, ewe, goat, swine, and bitch. However, there is no previous report that has documented a completely divided female genital tract in she-camel. Moreover, there is a lack of literature regarding this anomaly in animals. Therefore, the present study reports, for the first time, a rare case of a completely divided female genital tract in a she-camel. In addition, the existing relevant literature on uterus didelphys in different animal species is reviewed. Case presentation A female reproductive tract of she-camel, approximately 10 years old, with a history of previous successful pregnancy, was brought to the anatomy department following the slaughtering of the animal. Initial examination revealed a normal reproductive tract consisting of two ovaries, two fallopian tubes, a uterus, and a vagina. A closer examination revealed a completely divided vagina, with an external os opened into each part of the vagina, as well as a divided uterine body and cervix. Intrauterine infusion of saline through one external os confirmed complete separation of uterine body and cervix. Conclusion To the authors’ knowledge, this is the first reported case of a completely divided female genital tract in a she-camel. This review summarizes the previous reports about uterus didelphys in farm animals.